Development of rational formula to predict the advance and recession flow in border irrigation method - MARY REGINA F; Dr. A. N. Remadevi (Guide) (Tavanur 1992 Kelappaji college of Agricultural Engineering and Technology)
Development of rational formula to predict the advance and recession flow in border irrigation method
Development of rational formula to predict the advance and recession flow in border irrigation method